Postdigital Reading Strategies in Emersive VR Fiction: Empirical Insights - Alice Bell; Astrid Ensslin (Anglica. An International Journal of English Studies)
In this article we introduce a theory of ambimedial reading as a distinctive postdigital reading strategy from an empirical study with readers of Virtual Reality (VR) fiction. VR is known for its immersive, experiential qualities yet less for its affordances for literary fiction and verbal art. In experimental VR fiction, 360-degree, fully embodied spatial experiences can engender diverse ontological spheres, leaving readers straddling multiple diegetic and extradiegetic layers of storytelling. These ontological ruptures, evoked by what we call ambispatial design, can lend VR fiction an emersive quality, constructing readers as self-conscious voyeurs rather than granting them an unreflected, immersive experience. To illustrate these emersive effects, we consider participants’ discursive responses to reading Randall Okita’s VR memoir, The Book of Distance. We show how readers attempt to make sense of an unfamiliar postdigital storytelling experience by means of ambimedial responses, in which they attempt to reconcile an unfamiliar medial experience with more familiar ones. Our data shows that emersed readers conceptualize their doubly embodied and hybridized position as a constituent of both the actual world and digital VR world, a phenomenon we refer to as dual embodied metalepsis.